Hierarchical routing protocol in wireless sensor network: a state-of-the-art review. (4th May 2020) - Fang, Weidong; Zhang, Wuxiong; Shan, Lianhai; Assefa, Biruk; Chen, Wei
The hierarchical routing protocol in the wireless sensor network (WSN) is widely applied because of its good network stability and effective communication capability. Its cluster structure and the integration process of the data have a satisfactory performance in energy consumption and data transmission. To guide the design of hierarchical routing protocol, in this paper, we review the current research on these protocols, some typical technical characteristics such as the cluster head selection, clustering, and data routing are analysed, and a suggestion on the direction of the hierarchical routing protocol research is given. The work of this paper will be beneficial to the research, design, and optimisation of the hierarchical routing protocol.